Promoting Positive Masculinities to Address Violence Against Women: A Multicountry Concept Mapping Study - Daoud, Nihaya (Journal of interpersonal violence, 2023)
Interventions engaging men that challenge unequal gender norms have been shown to be effective in reducing violence against women (VAW). However, few studies have explored how to promote anti-VAW positive masculinity in young adults. This study aims to identify key multicountry strategies, as conceived by young adults and other stakeholders, for promoting positive masculinities to improve gender equity and prevent and target VAW. This study (2019–2021) involved young adults (aged 18–24 years) and stakeholders from Ireland, Israel, Spain, and Sweden. We applied concept mapping, a participatory mixed-method approach, in phases: (1) brainstorming, using semi-structured interviews with young adults (n = 105) and stakeholders (n = 60), plus focus group discussions (n = 88), to collect ideas for promoting anti-VAW positive masculinity; (2) development of an online questionnaire for sorting (n = 201) and rating ideas emerging from brainstorming by importance (n = 406) and applicability (n = 360); (3) based on sorting and rating data, creating rating maps for importance and applicability and clusters/strategies using multidimensional scaling and hierarchical cluster analysis with groupwisdom™ software; and (4) interpretation of results with multicountry stakeholders to reach agreement. The cluster map identified seven key strategies (41 actions) for promoting anti-VAW positive masculinities ranked from highest to lowest: Formal and informal education and training; Preventive education and activities in different settings/areas; Skills and knowledge; Empathy, reflection, and understanding; Media and public efforts; Policy, legislation, and the criminal justice system; and Organizational actions and interventions. Pattern matches indicated high agreement between young people and stakeholders in ranking importance (r = 0.96), but low agreement for applicability (r = 0.60). Agreement in the total sample on prioritizing statements by importance and applicability was also low (r = 0.20); only 14 actions were prioritized as both important and applicable. Young people and stakeholders suggested seven comprehensive, multidimensional, multi-setting strategies to facilitate promoting positive masculinity to reduce VAW. Discrepancy between importance and applicability might indicate policy and implementation obstacles.